ANALISIS PRODUKTIVITAS TENAGAKERJAPADA PEKERJAAN PEMANCANGAN TIANG PANCANG - JULIANSYAH, AKHMAD (KURVA S JURNAL MAHASISWA, 2013)
Akhmad Juliansyah, 2013, Analysis of Labor Productivity At Work Piling (Road Construction Project Case Study approach Pile Slab Bridge Build Ing Martadipura City District), Thesis, Department of Civil Engineering, Faculty of Engineering, University August 17, 1954 Samarinda.Konrtruksi services, labor productivity is one of the factors determining the success of a development project. In measuring the level of labor productivity there are a variety of ways, one of which is to examine the level of LUR (Labour Utilitation Rate) of each worker, which examined the extent to which the effectiveness of workers in the work. The level of labor productivity is influenced by many factors, including the condition of the field and aids, worker skills, the factors of age or the age of workers, wages suitability, experience in work, coordination and planning.The purpose of this study was to determine the level of labor productivity and determine the effect of field conditions and aids, worker skills, the factors of age or the age of workers, wages suitability, experience in work, coordination and planning, the level of labor productivity. The research was conducted in the approach bridge construction project Slab Bridge Pile Martadipura Ing Sub City Build The study was conducted by observing the level of labor productivity of 30 and accompanied by questionnaires. Observation level of productivity (LUR) conducted over 3 days for each worker. From the results of data collection, data questionnaires done productivity and data processing with the help of the computer program SPSS (Statistical Package for Social Science) version 19.From the data analysis that has been done can be seen that the level of productivity (LUR) the average worker on the roof of the structure of employment in Construction project approach Pile Slab Bridge City District Build Ing Martadipura of 66.8%, meaning quite productive because more than 50%. Predetermined variables turned out to signify 0.092> 0.005 (sig required) then simulatan no effect on the level of productivity. In partial yamg significant influence is the experience of working with sig = 0.001 <0.005 and worker skills sig = 0.002 <0.005. Work experience has a dominant influence with a beta value of 0.579.